LEGAL AUDIT QUALITY AND FRAUD RISK: THE CASE OF TUNISIAN LISTED COMPANIES - Lajmi, Azhaar; Khiari, Wided; Ouertani, Oumaima (International Journal of Accounting & Finance Review, 2021)
The aim of this study is to examine the impact of legal audit quality on the likelihood of accounting fraud, for a sample of 48 companies listed on the Tunisian stock market over the period between 2014 and 2018. Based on the logit panel regression, we have shown that the audit firm’s membership in one of the Big networks and the rotation of external auditors are two major determinants in the reduction of cases of fraud in Tunisian companies. In addition, the results showed that joint audit deteriorates the quality of auditing and thus increases the risk of fraud. This study provides new insights in terms of legal audit and fraud risk in the Tunisian context based on the econometrics of panel data, which is a valuable method to measure the impact of several actions alone or simultaneously. It has allowed us to analyze the behaviors of companies by considering the effect of many proxies of legal audit quality. JEL Classification Codes: G32, M42, C23.